Post-Depositional Fluid Flow in Jurassic Sandstones of the Uncompahgre Uplift: Insights From Magnetic Fabrics - Ejembi, John I.; Ferré, Eric C.; Satolli, Sara; Friedman, Sarah A. (Frontiers in Earth Science, 2020)
The anisotropy of magnetic susceptibility (AMS) in sedimentary rocks results from depositional, diagenetic, syn- and post-sedimentary processes that affect magnetic grains. Some studies have also shown the potential role played by post-depositional fluid flow in detrital and carbonate formations. Here we present a new case study of Middle-Upper Jurassic sandstones where secondary iron oxides, precipitated from fluids that migrated through pores, give rise to the AMS. These sandstones are well exposed in the Uncompahgre Uplift region of the Central Colorado Trough, Colorado. The magnetic foliation of these undeformed, subhorizontal strata consistently strike NE-SW over a large distance with an average 45° dip to the SE. This steep AMS fabric is oblique with respect to the regional subhorizontal bedding and therefore does not reflect the primary sedimentary fabric. Also, outcrop-scale and microscopic observations show a lack of post-depositional plastic (undulose extinction) or pressure-solution (stylolites) deformation microstructures in these sandstones, hence precluding a tectonic origin. The combination of magnetic hysteresis, isothermal remanent magnetization, and thermal demagnetization of the natural remanent magnetization indicate that these rocks carry a chemical remanent magnetization born primarily by hematite and goethite. High-field magnetic hysteresis and electron microscopy indicate that detrital magnetite and authigenic hematite are the main contributors to the AMS. These results show that post-depositional iron remobilization through these porous sandstones took place due to the action of percolating fluids which may have started as early as Late Cretaceous along with the Uncompahgre Uplift. The AMS fabric of porous sandstones does not systematically represent depositional or deformation processes, and caution is urged in the interpretation of magnetic fabrics in these types of reservoir rock. Conversely, understanding these fabrics may advance our knowledge of fluid flow in porous sandstones and may have applications in hydrocarbon exploration.